The significance of reworked palynomorphs (middle Cambrian to Tournaisian) in the Visean Toca da Moura Complex (South Portugal). Implications for the geodynamic evolution of Ossa Morena Zone - Lopes, Gilda (2014)
The 404.5 m deep SDJ1 borehole is located in the Jongeis mining sector of the Santa Susana Basin (SSB), and has been palynostratigraphically studied. The SSB is a Carboniferous coal-bearing basin developed along the suture contact between the Ossa Morena Zone (OMZ) and the South Portuguese Zone (SPZ).